Sistem Informasi Manajemen dalam Intelijen Bisnis - Deffari, Tantri; Irwan Padli, Muhammad; Ayu Sundari, Suci (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Management information systems in business intelligence can be said to process and analyze data related to business, the purpose of which is to assist businesses in making the right decisions. Business intelligence allows organizations to manage data, and turn it into information so that it is not fixated on numbers alone. However, businesses can better assess and improve their performance, budget cost-effectively, and find new business prospects when using business information. Many other elements affect sales besides the price and quality of the goods, such as the nature of the buyer, geographical factors, and other aspects. These reasons make business intelligence work very important. Business intelligence is one of them where business people or companies need tools. This business intelligence processes data into information about the products offered so that business people or companies can later make assessments.